Tarek Pukat Dance Aceh : the Form of Expression of Aceh Coastal Area Society Life - Fitriani, Fitriani; Hartono, Hartono; Triyanto, Triyanto (Catharsis, 2018)
Tarek pukat dance was created by Yuslizar in 1958. At the beginning, this dance is created to enliven the spirit of Aceh society in the Aceh youth congress that must be proud of Aceh’s land fertility. Tarek pukat dance is inherited through a learning process in Cut Nyak Dhien dance studio. This dance tells about how Aceh society life in the coastal area. Tarek pukat dance is usually performed by 5-9 female dancers, and 4 or 5 male dancers. Based on the information above, the purpose of this research was to observe the expression of Aceh coastal area society as a learning medium of Tarek Pukat dance. The method used in this research was qualitative. The research was located in Cut Nyak Dhien dance studio in Banda Aceh Anjong Mon Mata, in Banda Aceh Regency area. The data collection technique used was observation, interview, and document study. The data validity technique was source triangulation. The data analysis technique used was analysis descriptive. The results that Tarek Pukat dance through movements and properties, such as, peuget pukat, tarek pukat,kayoeh,ikat taloe,pasoe engkot lam raga, puwoe engkot as the expression of Aceh coastal area society. Based on the above matters, it can be said that Tarek Pukat dance builds a cooperative social character, optimistic, consistence, and loyality.